2000
DOI: 10.1097/00007632-200005010-00020
|View full text |Cite
|
Sign up to set email alerts
|

Os Odontoideum With Cerebellar Infarction

Abstract: Atlantoaxial instability may cause insufficiency of the vertebral artery as well as spinal cord injury. More attention should be paid to the possible relation between atlantoaxial instability and vertebrobasilar artery insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…OO has also been implicated in the development of cerebellar infarction [ 38 ]. Three-dimensional (3D) computed tomographic (CT) angiography showed that atlanto-axial dislocation resulted in the irregular narrowing of the vertebral artery, so the endothelium there is a likely focus for embolus formation [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…OO has also been implicated in the development of cerebellar infarction [ 38 ]. Three-dimensional (3D) computed tomographic (CT) angiography showed that atlanto-axial dislocation resulted in the irregular narrowing of the vertebral artery, so the endothelium there is a likely focus for embolus formation [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…The potential profits of using recombinant human bone morphogenetic protein-2 (rhBMP-2) over auto graft or allograft bone are abundant; they may contain reduced operational time, blood loss, donor-site morbidity, transmission of infection because of allograft, and rate of pseudarthrosis (77,78). On junction with adjuvant bone marrow aspiration or biological agents that comprise precursor cells to promote osteogenesis, and in some cases osteo induction, provide the required elements for osseous fusion (68,69,(79)(80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with atlantoaxial dislocation often report dizziness and vertigo in relation to head movement or positional changes (Vinchon et al, 1995;Wenngren et al, 1998). Other pathology, albeit extremely rare, that predisposes to atlantoaxial instabilty is aplasia of the odontoid proccss (Phillips et al, 1998), in which the vertebral artery is stretched by the subluxation of the atlas and os odontoideum (Lyness andSimeone, 1978: Takakuwa et al, 1994;Sasaki et al, 2000). Arnold-Chiari malformation is a congenital abnormality resulting in tht: herniation of the tonsils of the cerebellum and medulla oblongata through the foramen magnum into the vertebral canal.…”
Section: Cervical Spine Pathologymentioning
confidence: 99%
“…Another pathology that should be considered a contraindication, albeit extremely rare, is aplasia of the odontoid process (Phillips et al, 1998), in which the vertebral artery is stretched by the subluxation of the atlas and os odontoideum (Lyness and Simeone, 1978;Takakuwa et al, 1994;Sasaki et al, Patients sustaining whiplash injuries may experience symptoms for varying lengths of time. The symptoms can be located in the neck, face, upper trunk, arms, and hands.…”
Section: Humphr~ss/baanduley/sparkes~peerman/moffatmentioning
confidence: 99%